If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5 + -3y) = 84 (5 * 6 + -3y * 6) = 84 (30 + -18y) = 84 Solving 30 + -18y = 84 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -18y = 84 + -30 Combine like terms: 30 + -30 = 0 0 + -18y = 84 + -30 -18y = 84 + -30 Combine like terms: 84 + -30 = 54 -18y = 54 Divide each side by '-18'. y = -3 Simplifying y = -3
| 5x+50y=16 | | 20.50x+150=903 | | 30x+9=24+14x | | 4x-2(x-2)=-3+4x-1 | | 4(x-6)=-3-7 | | 2x-14y-20=0 | | 2.3x+4.8=9 | | 20.50x+150+343=903 | | -3x^2+5=10 | | 18x+14=18x+15 | | 7*n=41 | | 4c-6=-18 | | -5x^2-3x+12=10 | | 3h-9-8h=11 | | 800+2x=650+5x | | 3(4x+2)=5(2x-3) | | 24-24y=6 | | 2x^2-3x+4=-5 | | 10x+2x=(10+2)x | | 2x^2-13x-34= | | 2(m+2)+3=11 | | 2ysquared=392 | | 8-3x=8x-3x+16 | | 25y^2-81z^2=0 | | 9w^2+48wu+64u^2=0 | | -3x+11x-122=78 | | 6x^2+4x-8=2 | | -3y-20y+32=-6-5+5y | | -6*3y= | | 3(q+5)=3q+15 | | (14y+2y)-5y= | | 6m-40=2m |